2013
DOI: 10.1590/s2176-94512013000300004
|View full text |Cite
|
Sign up to set email alerts
|

The four mechanisms of dental resorption initiation

Abstract: O presente trabalho propõe-se a apresentar uma classificação, com aplicação clínica, para as reabsorções dentárias, para que o diagnóstico seja objetivo e imediatamente ligado à causa do problema, levando automaticamente o clínico ao provável plano de tratamento e a um prognóstico preciso. Com esse objetivo, sugerimos agrupar cada caso clínico de reabsorção dentária em um dos seguintes grupos: 1) Reabsorções radiculares pela morte dos cementoblastos, com manutenção dos restos epiteliais de Malassez.2) Reabsorç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 0 publications
3
15
0
11
Order By: Relevance
“…Depending on the type and intensity of dental trauma, some areas of periodontal ligaments can mortify, and during the healing process, these areas can be colonized by bone cells 20 . The initiation of an inflammatory process-for example, due to orthodontic movement-can initiate external root resorption because these bone cells have receptors for these mediators of inflammation and may provide basic multicellular units (BMU) that will initiate the tooth resorption 18,20 This demonstrates the importance of care in orthodontic movement after dental trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type and intensity of dental trauma, some areas of periodontal ligaments can mortify, and during the healing process, these areas can be colonized by bone cells 20 . The initiation of an inflammatory process-for example, due to orthodontic movement-can initiate external root resorption because these bone cells have receptors for these mediators of inflammation and may provide basic multicellular units (BMU) that will initiate the tooth resorption 18,20 This demonstrates the importance of care in orthodontic movement after dental trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, root canal treatment was performed as the standard procedure to control the infection of endodontic origin . For the gingival and periodontal routes, we followed the recommendation of root surface treatment combining removal of the necrotic PDL remnants, immersion in a sodium fluoride solution, and administration of systemic antibiotics . Calcium hydroxide intracanal dressing was used because of its well‐known biological and antimicrobial properties and its wide use in tooth replantation .…”
Section: Discussionmentioning
confidence: 99%
“…Delayed tooth replantation is far more frequent than immediate replantation. One of the causes is people's and even dentists' lack of knowledge of the adequate management of cases of avulsion , which results in extensive damage to PDL, including death of cementoblasts and necrosis of the precementum layer and the epithelial cell rests of Mallassez, starting a resorption process .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that internal resorption proceeded mainly due to chronic inflammation in the pulp, loss of/or damage to the odontoblasts and the predentin. [17][18] Furthermore, the invasion of macrophage into the pulp also responsible for internal root resorption. In the advance cases, the pulp tissue apical to the resorptive lesion undergoes necrosis and the bacteria infect the entire root canal system resulting in acute or chronic apical periodontitis followed by formation of sinus tract with suppuration in the periapical tissue or possibly at the site of perforation of the root canal wall caused by the hard tissue destruction.…”
Section: Pathogenesismentioning
confidence: 99%